District-University Collaborations to Support Reform-Based Mathematics Curriculum - Kelly Gomez Johnson; Amy L. Nebesniak; Theodore J. Rupnow (Journal of Mathematics Education at Teachers College, 2019)
Curriculum change is inevitable in schooling. For content areas such as mathematics that are already under the national spotlight, transitioning to new curriculum materials while concurrently enacting instructional reform creates both a challenge and an opportunity. This paper discusses how partnerships between two state universities and respective neighboring school districts resulted in the creation and implementation of graduate courses for teachers targeted at curricular and instructional reform specific to each district. Common course components between both university-district partnerships were identified in the areas of mathematics research, practice, and leadership advocacy and found to be instrumental in supporting instructional reform and fostering sustained development. Implications for collaborative partnerships, curriculum implementation and research are discussed.